Impact of weather and climate on seed protein and oil content of soybean in the North Сaucasus - L. Yu. Novikova; I. V. Seferova; A. Yu. Nekrasov; I. N. Perchuk; T. V. Shelenga; M. G. Samsonova; M. A. Vishnyakova (Вавиловский журнал генетики и селекции)
For a targeted search of initial breeding material for the quality of soybean seeds, it is necessary to know the patterns of the dependence of the corresponding seed characters on the weather and climatic conditions in a particular region. Global climatic change, the concretization of which is relevant, has a share in this dependence. Thus, the aim of this work was to identify the relationship between the variability of protein and oil content in soybean seeds with climatic parameters in the North Caucasus as well as trends in this variability over a long time period. The study of 1 442 soybean accessions from VIR collection in the Krasnodar region during 1987–2015 had been carried out and the tendencies of the variability of protein and oil content in seeds in this environment were estimated. The regression analysis in differences with forward stepwise selection of variables has been used to construct models for the dependence of the protein and oil content on generalized agrometeorological indices. During 1987–2015, for the period with temperatures above 10 °C, the sums of active temperatures increased by 218 °C/10 years and precipitation decreased by 20.9 mm/10 years. In the dynamics of protein content, a trend has been revealed as an increase by 2.5 % over 10 years, while there is no reliable trend in oil content. The maximum average mean of oil content and the smallest protein were in the middle-maturing accessions (22.2 and 38.8 %), and a relatively high protein content was detected, on average, in the early- (21.6 and 40.0 %) and late-maturing (20.2 and 39.9 %) varieties. The protein content had been increasing with a growth of the duration of the period with temperatures above 22 °C and decreasing with a raise in precipitation over a period of temperatures above 18 °C. The accumulation of oil in seeds was promoted by an increase of the hydrothermal coefficient over the period with temperatures above 19 °C, and, in late-maturating varieties, prevented by a prolonged autumn period with temperatures below 15 °C. Long-term growth in protein content is due to both climatic change and genetic improvement of varieties.